Effects of ozone therapy applied topically, by bagging, or both on the healing of clean wounds induced in rat’s skin - Bárbara Di Martino Frezza; Sheila Canevese Rahal; Ivan Felismino Charas dos Santos; Bruna Martins da Silva; José Ivaldo de Siqueira Silva Junior; Gustavo Manea Ferreira; Michel de Campos Vettorato; Jéssica Leite Fogaça; Miriam Harumi Tsunemi; Carlos Eduardo Fonseca-Alves; Claudia Helena Pellizzon; Vinicius dos Santos Rosa (Acta Cirúrgica Brasileira, 2024)
ABSTRACT Purpose: This study aimed to evaluate the effects of ozone therapy applied topically and/or by bagging on the healing of clean wounds induced in rat’s skin. Methods: One hundred and twenty male rats of about 16 weeks old was divided into five groups: G1) saline solution (0.9%); G2) sunflower oil; G3) ozonated sunflower oil; G4) ozone bagging; G5) association of ozonated sunflower oil and ozone bagging. The wounds were evaluated through macroscopic, morphometric, histopathologic, and tensile strength analyses. Results: Analysis among groups showed a lower percentage of wound contraction in G1 compared to G4 only in M7D. The tensile strength of the wounds showed differences among groups in the seventh (M7D) and the 14th (M14D) postoperative day, and among time points in G1 (M14D > M7D). The elongation of the wounds showed differences in G3 (M7D > M14D). Histological evaluation of the wounds showed significant change in bleeding, mixed to mononuclear infiltrate, congestion, and tissue disorganization for tissue organization between groups and time points. Conclusions: Ozone therapy applied topically and/or by bagging was not deleterious to the healing of clean wounds induced in rat’s skin, but ozone bagging showed the best contribution to the healing process.